The Replication of Mutually Supportive Social Networks in an On-Line Environment and How Community Electronic Networks Can Be Used as a Space for Learning - Squire, David (Proceedings of the International Conference on Networked Learning, 1998)
Within community education practice there is a recognition that learning occurs in social, informal environments and through learners developing peer relationships. For an adult, returning to education is as much about meeting people with similar interests and goals as it is about the focused, formal study that goes on. Adults learn through talking and listening, and these social dynamics help build learning communities. The dissertation will consider how these mutually supportive social networks can be replicated in an on-line environment and how the rise of community electronic networks can be used as a space for learning. It will look at the nature of virtual communities and on-line group dynamics and how a conducive setting for informal learning and social networking can be created.